Ideological Prophetic Leadership in Transnational Islamic Educational Organizations - Khudin, Ilham Soleh; Noor, Farhan; Aznar, Maulana (Jurnal Pendidikan Agama Islam Indonesia (JPAII), 2026)
Purpose of the study: This study aims to examine how transnational Islamic ideology shapes leadership construction, governance structures, and authority legitimacy within educational institutions, and to formulate an integrative conceptual model explaining the relationship between ideological foundations and educational leadership practices. Methodology: This study employed a qualitative multiple-case design using in-depth semi-structured interviews, non-participant observation, and document analysis. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, supported by thematic coding procedures. Institutional statutes, policy documents, and scholarly literature were reviewed to strengthen triangulation and analytical validity. Main Findings: The findings show that leadership in transnational Islamic educational institutions is constructed upon theological legitimacy, ideological alignment, structured consultation, and moral-exemplary authority. Governance mechanisms integrate doctrinal commitment with formal administrative systems, forming hybrid models that balance transnational ideological orientation with national educational regulations. Leadership functions as a strategic instrument for ideological reproduction and institutional identity consolidation. Novelty/Originality of this study: The findings show that leadership in transnational Islamic educational institutions is constructed upon theological legitimacy, ideological alignment, structured consultation, and moral-exemplary authority. Governance mechanisms integrate doctrinal commitment with formal administrative systems, forming hybrid models that balance transnational ideological orientation with national educational regulations. Leadership functions as a strategic instrument for ideological reproduction and institutional identity consolidation.